Legal Education xMOOCs – A Mirage in the Australian Regulatory Environment? - Stephen Colbran; Scott Beattie; Anthony Gilding (Legal Education Review)
Legislative studies are a sub discipline of law that explores legislation, as a process and as a product, including the legislative environment in its widest sense. Within this context, the nature of legislative drafting as art, craft, science or mere process has been much debated. Nowadays, legislative drafting is considered a ‘phronetic’ area of law that combines elements of art and science and requires at the same time creativity, innovation and knowledge of theory. Taking a bottom up approach informed by the profile, role of drafters and educational theories, this paper proposes a 'phronetic', approach to the teaching of legislative drafting that combines three main elements: theoretical training on acknowledged drafting rules and conventions; practical experience to familiarize the trainee drafter with the decisions that need to be made in the process of designing a specific legislative text; and experimentation and reflective practice that allow the drafter to become creative and independently thinking.